Accounting and Accounting Policy Отчетность и учетная политика предприятия - Demidenko Leonid P. (Bìznes Inform, 2013)
The article considers essence and contents of accounting policy. Its provides information with respect to main aspects of formation and application of accounting policy in Ukraine. It studies the structure of regulations on accounting policy that were developed in a company. It specifies correlation of accounting policy and organisation of accounting. It explains the determining role of the top manager and chief accountant in formation of accounting policy of a company. It identifies regulation of main components of accounting policy. It justifies interrelation of accounting and accounting policy. В статье рассмотрена суть и содержание учетной политики. Подана информация относительно основных аспектов формирования и применения учетной политики предприятий в Украине. Исследована структура разработанного на предприятии положения об учетной политике. Уточнено соотношение учетной политики и организации бухгалтерского учета. Освещена определяющая роль, которая принадлежит руководителю и главному бухгалтеру в формировании учетной политики предприятия. Определено регулирование основных составляющих учетной политики предприятия. Обоснована взаимосвязь бухгалтерского учета и учетной политики.